PELAKSANAAN KLAUSUL PERMOHONAN TIDAK BERITIKAD (VEXATIOUS REQUEST): STUDI KOMPARASI DI BEBERAPA NEGARA - Priatna, Achmad Nashrudin (LPPM Universitas Bina Bangsa, 2024)
In the Era of Public Information Disclosure, with the birth of Law No. 14 of 2008 concerning Public Information Disclosure, obtaining public information is a public right or public right. To obtain public information from a public agency (a public agency is an institution funded by the state budget (APBN) or the regional budget (APBD) or other institutions with funding sources from public contributions and foreign aid), it must follow public information service standards (SLIP). However, there are times when the public requests a large amount of information to a public agency at the same time. So that it is indicated that it does not have good faith and is not serious, called vexatious request. The same thing is also found in some countries, although with different contexts and consequences. In addition to vexatious requests, the termsrepeated request and frivolous request are also known. This article aims to determine the implementation of the principle of requests that are not in good faith or earnest. The method used is descriptive analysis